l-Isoaspartyl Methyltransferase Deficiency in Zebrafish Leads to Impaired Calcium Signaling in the Brain - Soliman, Remon; Cordero-Maldonado, Maria Lorena; Martins, Teresa G.; Moein, Mahsa; Conrotte, Jean-François; Warmack, Rebeccah A.; Skupin, Alexander; Crawford, Alexander D.; Clarke, Steven G.; Linster, Carole L. (Frontiers in Genetics, 2021)
Isomerization of L-aspartyl and L-asparaginyl residues to L-isoaspartyl residues is one type of protein damage that can occur under physiological conditions and leads to conformational changes, loss of function, and enhanced protein degradation. Protein L-isoaspartyl methyltransferase (PCMT) is a repair enzyme whose action initiates the reconversion of abnormal L-isoaspartyl residues to normal L-aspartyl residues in proteins. Many lines of evidence support a crucial role for PCMT in the brain, but the mechanisms involved remain poorly understood. Here, we investigated PCMT activity and function in zebrafish, a vertebrate model that is particularly well suited to analyze brain function using a variety of techniques. We characterized the expression products of the zebrafish PCMT homologous genes pcmt and pcmtl. Both zebrafish proteins showed a robust L-isoaspartyl methyltransferase activity and highest mRNA transcript levels were found in brain and testes. Zebrafish morphant larvae with a knockdown in both the pcmt and pcmtl genes showed pronounced morphological abnormalities, decreased survival, and increased isoaspartyl levels. Interestingly, we identified a profound perturbation of brain calcium homeostasis in these morphants. An abnormal calcium response upon ATP stimulation was also observed in mouse hippocampal HT22 cells knocked out for Pcmt1. This work shows that zebrafish is a promising model to unravel further facets of PCMT function and demonstrates, for the first time in vivo, that PCMT plays a pivotal role in the regulation of calcium fluxes.